KARAKTERISTIK PASIEN KANKER SERVIKS DI RSUD DR. SOETOMO SURABAYA PERIODE JANUARI – DESEMBER 2017 - Ahmad Fahrur Rozi; Dwi Susanti; Jimmy Yanuar Annas (Majalah Biomorfologi, 2019)
Background: Cancer is one of mortality and morbidity throughout the world. The prevalence of cancer incidence in the world is still ranked highest after cardiovascular disease. In 2012 there were around 14 million new cancer cases and is estimated to increase around 70% over the next two decades. In Indonesia cervical cancer is cancer with highest numbers after breast cancer in women.Objective:This study aims to observe characteristics of age, marital status and clinical stage in patients with a diagnosis of cervical cancer. Material and method: The sample was all medical record of cervical cancer patients who had been treated at the Inpatient room/Obstetrics and Gynecology Installation in RSUD Dr. Soetomo Surabaya in period of January - December 2017. All patient’s medical record with cervical cancer within this period are incuded in research samples. The collected data is processed according toage, marital status and clinical stage cervical cancer. Then tabulation of data and descriptive statistical analysis of data that has been obtained. Result:The results of the study found 521 patient’s complete and unduplicated data including the age group diagnosed with cervical cancer, marital status and patient clinical stage. Conclusion: From the results of research regarding the characteristics of patients with cervical cancer diagnosis obtained information that the most age group is in the age range of 51-60 years (38.2%), almost 97.5% of married patients and mostly patients with cervical cancer are in the stage 3B (53.4%).